2021
DOI: 10.3390/nu13051569
|View full text |Cite
|
Sign up to set email alerts
|

The TOTUM-63 Supplement and High-Intensity Interval Training Combination Limits Weight Gain, Improves Glycemic Control, and Influences the Composition of Gut Mucosa-Associated Bacteria in Rats on a High Fat Diet

Abstract: Obesity and prediabetes are the two strongest risk factors of type 2 diabetes. It has been reported that TOTUM-63, a polyphenol-rich plant extract, has beneficial effects on body weight (BW) and insulin resistance in mice fed a high fat diet (HFD). The study aim was to determine whether high-intensity interval training (HIIT) and/or TOTUM-63 supplementation improved body composition and glycemic control and gut microbiota composition in a Western diet-induced obesity rat model. Wistar rats received a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 81 publications
1
32
0
Order By: Relevance
“… 37 TOTUM-63 (T-63) is a polyphenol-rich plant extract that can have beneficial effects on the body weight and the insulin resistance in mice on a high-fat diet (HFD). 38 The combination of high-intensity interval training (HIIT) and T-63 was applied to a Western diet-induced obesity rat model, and it was found that this combined modality significantly limited the weight gain and improved the blood glucose levels in the rats, while their Oscillospira abundance was also significantly increased. 38 Green tea polyphenols (GTP) can also improve the abundance of Oscillospira in the gut of female sprague-dawley rats.…”
Section: Factors Affecting the Abundance Of Oscillospiramentioning
confidence: 99%
“… 37 TOTUM-63 (T-63) is a polyphenol-rich plant extract that can have beneficial effects on the body weight and the insulin resistance in mice on a high-fat diet (HFD). 38 The combination of high-intensity interval training (HIIT) and T-63 was applied to a Western diet-induced obesity rat model, and it was found that this combined modality significantly limited the weight gain and improved the blood glucose levels in the rats, while their Oscillospira abundance was also significantly increased. 38 Green tea polyphenols (GTP) can also improve the abundance of Oscillospira in the gut of female sprague-dawley rats.…”
Section: Factors Affecting the Abundance Of Oscillospiramentioning
confidence: 99%
“…A growing body of evidences shows that HIIT is a time-efficient exercise mode for losing total and (intra)abdominal FM [8,58,59] and for reducing obesity-induced OS [20,28,60,61]. As already mentioned by [30], the 12-week HIIT program, but not LO supplementation, changed body composition (by limiting weight and FM gain and by decreasing adipocyte size in the mesenteric and subcutaneous adipose tissues only).…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the HIIT program alleviated HFD negative effects in liver by reducing SOD activity, and also by decreasing the activity of the pro-oxidant enzyme NOx. In animals, very few studies have tested the effects of a HIIT program on obesity-induced OS [20,58,60,61]. Among those using HFD to induce obesity [58,60,61], there is no consensus on HIIT effect on the pro/antioxidant status because the HFD-induced OS alterations differed among studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a translational study indicated that T63 can reduce body weight, control glucose homeostasis, and may protect against type 2 diabetes [84]. Accordantly, recent studies based on obese rodent models have shown that T63 supple-mentation improves glycemic levels by inducing skeletal muscle oxidative capacity [85], decreases inflammation, and improves insulin sensitivity [86], suggesting that T63 might be a promising novel nutritional supplement against obesity. Figure 1 summarizes the molecular mechanisms underlying the anti-obesity effects of the main polyphenols.…”
Section: Polyphenol Effect On Obesitymentioning
confidence: 99%